Interaction between mitochondrial quality control and metal-mediated cell death in sepsis and its clinical significance - Zhou Qiyuan; Li Jingyan; Tian Yingping; Yao Yongming (生物医学转化)
Sepsis is defined as life-threatening organ dysfunction caused by a dysregulated host response to infection. Its progression is closely associated with metal metabolism abnormalities and mitochondrial quality deterioration. Mitochondria serve as centers for energy metabolism and metal storage, and their quality control regulates metal-mediated cell death, influencing the progression of sepsis. This review discusses the mechanisms of mitochondrial quality control (MQC) and their relationship with metal-induced cell death. It explores the effects of metal metabolism and MQC changes on cell death under septic conditions. The interaction between these factors is further examined for its significance in the pathophysiological processes of sepsis and related complications. This paper provides new insights for its diagnosis and treatment.